Coxsackievirus B3 Induction of NFAT: Requirement for Myocarditis Susceptibility - Huber, S. A. (2008)
Ultraviolet (u.v.) inactivated Coxsackievirus B3 (CVB3) induces rapid calcium flux in naïve BALB/c CD4+ T cells. CD4+ cells lacking decay accelerating factor (DAF-/-) show little calcium flux indicating that virus cross-linking of this virus receptor protein is necessary for calcium signaling in CVB3 infection. Interaction of CVB3 with CD4+ cells also activates NFAT DNA binding. To show that NFAT activation is crucial to CVB3 induced disease, wild type mice and transgenic mice expressing dominant-negative NFAT (dnNFAT) mutant in T cells were infected and evaluated for myocarditis and pancreatitis 7 days later. Inhibition of NFAT in T cells prevented myocarditis but had no effect on pancreatitis. Virus titers in pancreas were equivalent in wild-type and dnNFAT animals but cardiac virus titers were increased in dnNFAT mice. Interferon-gamma (IFNγ) expression was reduced in both CD4+ and Vγ4+ T cells from dnNFAT mice compared to controls. FasL expression by Vγ4+ cells was also suppressed. Inhibition of FasL expression by Vγ4+ cells is consistent with myocarditis protection in dnNFAT mice.